McGraw-Hill Concise Encyclopedia of Science and Technology, Sixth Edition (McGraw-Hill Concise Encyclopedia of Science & Technology) (Mc Graw Hill, 2008)
A major revision of this classic encyclopedia covering all areas of science and technology, the McGraw-Hill Concise Encyclopedia of Science and Technology, Sixth Edition, is prepared for students, professionals, and general readers seeking concise yet authoritative overviews of topics in all major fields in science and technology.